Towards Sustainable Pasture Agrolandscapes: A Landscape-Ecological-Indicative Approach to Environmental Audits and Impact Assessments - Roman Plokhikh; Dana Shokparova; Fodor Gyula; Berghauer Sándor; Tóth Attila; Uzakbay Suymukhanov; Aiman Zhakupova; Varga Imre; Kai Zhu; Dávid Lóránt Dénes; Фодор Дюло; Бергхауер Олександр; et al. (MDPI, 2023)
Abstract. Reliable environmental audits and impact assessments are essential to achieve effective pasture utilization and ensure the production of high-quality livestock products. This study aims to develop an environmental audit and impact assessment method for pasture agrolandscapes to promote sustainable livestock practices, using Central Kazakhstan as a case study. To provide a strong foundation for this research, the study utilized representations of pasture agrolandscapes, landscape-ecological and landscape-indicative approaches, and interactions between environmental audits and impact assessments in Kazakhstan. The authors acknowledge that their understanding of the environmental audit and impact assessment for pasture agrolandscapes is a complex method that requires specific knowledge and information about the landscape environment from users. They note that solving the challenges of national food security and environmentally safe territorial development can be achieved through the development of a private method that uses landscape environment status indicators. Methods similar to this enable the study of geocomplexes and their crucial characteristics, leading to a unique system of reliable indicators for environmental issues. This approach facilitates the creation of a scientifically based plan for optimal regional land use and land management systems regarding pasture agrolandscapes.
Keywords: environmental audit; impact assessment; pasture agrolandscapes; sustainable livestock practices